Embedded Ancient Greek Imperatives: A Feature Transfer Analysis. (13th March 2015) - Medeiros, David J.
Abstract: This paper presents an analysis of data in which imperative verbs appear in nonroot clauses, namely relative and finite verbal complement clauses. Although crosslinguistically rare, such embedding is well attested in languages such as Ancient Greek and Slovenian, and it is impossible in languages such as English. An analysis is presented in which rich imperative morphology is related to the possibility of embedding imperatives in CP contexts, which is formalized in terms of the independently motivated theory of Feature Transfer (Chomsky 2008). According to the analysis presented here, the difference between Ancient Greek and English imperatives is one of subcategorization, such that a ϕ‐complete C is able to subcategorize for imperative T in Ancient Greek but not in English. Rich imperative morphology, defined as having overt forms beyond the second person, is taken to be a necessary condition for the learner to posit that ϕ‐complete C can select imperatives, as in Ancient Greek but not in English. The analysis suggests a view of the grammar in which sentential force is encoded in the syntax, given that morphologically imperative verbs are disassociated with directive force in Ancient Greek.